Preinjury Patient Characteristics and Postinjury Neurological Status Are Associated With Mortality Following Spinal Cord Injury. Issue 13 (1st July 2018) - Casper, David S.; Zmistowski, Benjamin; Schroeder, Gregory D.; McKenzie, James C.; Mangan, John; Vatson, Jayanth; Hilibrand, Alan S.; Vaccaro, Alexander R.; Kepler, Christopher K.
Abstract : Study Design: Retrospective cohort study. Objectives: This study investigates the association between spinal cord injuries (SCI) and post-injury mortality. Summary of Background Data: SCIs) are severe conditions treated in the acute trauma setting. Owing to neurological deficits, unstable spinal columns, and associated injuries, these patients often have complex inpatient hospitalizations with significant morbidity and mortality. It is assumed that a high rate of postinjury mortality would follow such severe injuries; however, the effect of SCI and its treatment on predictors of longevity remain largely unknown. Methods: Patients seen at a regional referral center for SCI were reviewed from a prospectively maintained database. Four hundred and twenty-six patients with SCI and varying degrees of injury between 2004 and 2009 were collected. Injury characteristics, including injury severity score, level of SCI, and type of SCI were retrieved. To determine independent predictors of 5-year mortality, a logistic regression using patient and injury characteristics at the time of presentation was performed. Results: Average age was 47.4 years (range: 14–95), and 74.5% (318/426) were male. Half of the cohort sustained low-energy mechanisms of injury (220/426; 52.4%). The 30-day, 90-day, 1-year, 2-year, and 5-year mortality rates in the SCI cohort were 6.6% (28/426), 9.2% (39/426), 12.0% (51/426), 15.0% (64/426), and 17.8%, respectively (76/426). Logistic regression demonstrated that increasing age ( B = 1.06, P < 0.001), increasing ICU length-of-stay ( B = 1.06; P = 0.002), decreased motor score at presentation ( B = 0.98; P = 0.004), and lack of surgical intervention ( B = 0.38; P < 0.001) were independent predictors of mortality at 5 years. Conclusion: There is substantial mortality associated with SCI. A significant proportion of the mortalities occurred acutely after injury. Mortality was associated with neurological deficit and severity of injury, as well as with preinjury patient characteristics. To combat this high rate of death, efforts are needed to address the concomitant disease processes associated with neurological deficits. Level of Evidence: 3